Expression density of receptors to IL-1β in atopic dermatitis. (July 2016) - Alshevskaya, Alina A.; Lopatnikova, Julia A.; Krugleeva, Olga L.; Nepomnyschih, Vera M.; Lukinov, Vitaliy L.; Karaulov, Aleksander V.; Sennikov, Sergey V.
Highlights: Density of cytokine receptors expression needs to be studied in pathology. Changes in percentage of cells and number of receptors may be differently directed. IL-1β receptor expression is associated with disease severity in atopic dermatitis. Abstract: Interleukin 1 (IL-1 β) and the system for regulation of its biological effects play an important role in the development and behavior of inflammatory processes in atopic dermatitis. Notably, cells that are actively involved in the pathological process have altered expression of cytokine receptors. However, standard evaluation of cells by flow cytometry measures only the percentage of cells expressing the appropriate marker, which is not enough for a full assessment of these changes.The aim of this study was to investigate changes in the expression of IL-1β cytokine receptors in patients with atopic dermatitis by both percentage of cells with receptors in various subsets and the absolute number of membrane-bound receptors themselves. It was found that an increase or decrease in the percentage of cells expressing the receptors in subsets of immune cells in patients with atopic dermatitis was not associated with a change in the number of receptors on the cell surface. Moreover, the changes in the percentage of cells and the number of receptors may occur in different directions, as shown for IL-1R2 expression on B cells and IL-1R1 expression for monocytes. Changes in the parameters of IL-1β receptor expressions are associated with disease severity index SCORAD in atopic dermatitis. These findings underline the importance of studying the density of cytokine receptor expression in the pathology.